(untitled) (Conferencea, 2024)
The dynamic nature of network technologies necessitates a transformative approach to education that equips students with the relevant skills and knowledge. This thesis presents a comprehensive methodology aimed at enhancing the software and didactic support for teaching network technologies in higher educational institutions. By integrating hands-on learning experiences, aligning curricula with industry standards, and fostering continuous feedback mechanisms, this approach seeks to create a more engaging and effective educational environment.